2013
DOI: 10.3329/bjas.v42i1.15783
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat stress on blood parameter, carcass and meat quality of Black Bengal goat

Abstract: The research was conducted to study the effect of heat stress on blood parameter, carcass characteristics and meat quality of the Black Bengal goat. Nine goats were randomly and equally divided into three groups having almost same age and weight. Three groups were divided as zero hour (T0), four hours (T4) and eight hours (T8) of heat exposure. The T0 group were not exposed to heat stress, the T4 and T8 group were exposed to heat by keeping them at outside for 4 (four) hours and 8 (eight) hours from 9.00 AM to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 10 publications
(3 reference statements)
3
18
0
Order By: Relevance
“…The, HG did not varied significantly among both the control and heat stress groups. Similar results of non-significant influence of heat stress on HG were also established in Bengal goats (Hashem, Hossain, Rana, Islam, & Saha, 2013) and…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The, HG did not varied significantly among both the control and heat stress groups. Similar results of non-significant influence of heat stress on HG were also established in Bengal goats (Hashem, Hossain, Rana, Islam, & Saha, 2013) and…”
Section: Discussionsupporting
confidence: 79%
“…The, HG did not varied significantly among both the control and heat stress groups. Similar results of non‐significant influence of heat stress on HG were also established in Bengal goats (Hashem, Hossain, Rana, Islam, & Saha, ) and native Bangladesh sheep (Rana et al., ). This non‐significant difference in HG could be attributed to the adaptive capability of indigenous goats to heat stress conditions.…”
Section: Discussionsupporting
confidence: 70%
“… Zhu et al. (2011) and Hashem et al. (2013) found that muscles in a heat-stressed group had higher DL compared to non–heat-stressed controls ( P < 0.05).…”
Section: Resultsmentioning
confidence: 94%
“…Although goats are considered well adapted to the tropical climate, their adaptive responses significantly hamper their production [ 2 ]. Some studies established the impact of elevated ambient temperature on growth [ 20 ], milk production [ 31 ], meat production [ 19 , 32 ] and immune responses [ 33 ] in goats. These authors observed a reduction of 12%, 3–10%, and 4% for growth, milk and meat production, respectively.…”
Section: Heat Stress and Goat Productionmentioning
confidence: 99%